2007
DOI: 10.1099/vir.0.82618-0
|View full text |Cite
|
Sign up to set email alerts
|

Induction of nitric oxide synthase by rotavirus enterotoxin NSP4: implication for rotavirus pathogenicity

Abstract: Rotavirus non-structural protein (NSP) 4 can induce aqueous secretion in the gastrointestinal tract of neonatal mice through activation of an age-and Ca 2+ -dependent plasma membrane anion permeability. Accumulating evidence suggests that nitric oxide (NO) plays a role in the modulation of aqueous secretion and the barrier function of intestinal cells. This study investigated transcriptional changes in inducible NO synthase (iNOS), an enzyme responsible for NO production, after rotavirus infection in mice and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 47 publications
0
20
0
1
Order By: Relevance
“…NO secretion can be triggered in vitro and in vivo by rotavirus nonstructural protein 4 (NSP4) (2830), which in turn may cause diarrhea by elevating intestinal permeability (31, 32) and regulating intestinal motility (33) and intestinal ion transport (34, 35). In contrast to rotavirus infection (2830), little NO production was observed during PSaV replication in LLC-PK cells, possibly due to the synthesis of PGE 2 , suggesting that NO may not be involved in sapovirus-induced diarrhea. However, it is important to note that we cannot fully rule out a potential role for NO in PSaV pathogenesis in vivo , where the cellular response to infection is influenced by numerous cell types and may not be entirely reproduced in immortalized cells in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…NO secretion can be triggered in vitro and in vivo by rotavirus nonstructural protein 4 (NSP4) (2830), which in turn may cause diarrhea by elevating intestinal permeability (31, 32) and regulating intestinal motility (33) and intestinal ion transport (34, 35). In contrast to rotavirus infection (2830), little NO production was observed during PSaV replication in LLC-PK cells, possibly due to the synthesis of PGE 2 , suggesting that NO may not be involved in sapovirus-induced diarrhea. However, it is important to note that we cannot fully rule out a potential role for NO in PSaV pathogenesis in vivo , where the cellular response to infection is influenced by numerous cell types and may not be entirely reproduced in immortalized cells in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…To this end, we stimulated the cells with LPS and quantified the number of cells expressing the inducible NO synthase (Borghan et al, 2007). Treatment with LPS induced increased number of iNOS expressing cells and fluorescence intensity, but the quantity of iNOS- positive cells and the intensity of the staining did not differ between cells from both genotypes (Fig.…”
Section: Upregulation Of Inos In Response To Lps Is Not Affected By Tmentioning
confidence: 98%
“…Although it has not yet been proved whether iNOS activity is also relevant in controlling the infection in mice as happens in avian species and which cell type would produce it, it has been demonstrated that it plays a role in protecting mice from norovirus infection (143), suggesting that it might play a role against astroviruses as well. On the other hand, however, since NO has also been shown to regulate intestinal mucosal permeability and ion transport, a role of NO as a mediator of diarrhea caused by other viral infections such as rotaviruses has also been demonstrated (144,145).…”
Section: Host Immune Responses and Control Of Infectionmentioning
confidence: 99%